KRAS mutation in secondary malignant histiocytosis arising from low grade follicular lymphoma - Sarah M. Choi; Aleodor A. Andea; Min Wang; Amir Behdad; Lina Shao; Yanming Zhang; Xinyan Lu; David Dittmann; Juan Castro; Yi-Hua Chen; Juehua Gao (BMC, 2018)
Abstract Background Transformation of follicular lymphoma most typically occurs as diffuse large B-cell lymphoma, however other forms of transformation such as classic Hodgkin lymphoma and lymphoblastic transformation can occur. Secondary malignant histiocytosis also represents a rare form of transformation, which is thought to occur due to a process of transdifferentiation whereby the lymphoma cells exhibit lineage plasticity and lose all evidence of B-cell phenotype and instead acquire the phenotype of a histiocytic neoplasm. Little is known about the underlying genetic alterations that occur during this unusual process. Comparative genetic analysis of pre- and post-transformation/transdifferentiation would be one tool by which we could better understand how this phenomenon occurs. Case presentation Here we report the clinical, immunophenotypic and genetic features of a rare case of secondary malignant histiocytosis, Langerhans cell-type (Langerhans cell sarcoma) arising from a previous low grade follicular lymphoma. FISH analysis confirmed the presence of IgH/BCL2 rearrangement in both the low grade follicular lymphoma (FL) and transformed Langerhans cells sarcoma (LCS) samples, demonstrating a clonal relationship. Comparative whole exome sequencing was then performed, which identified a KRAS p.G13D mutation in the LCS that was not present in the FL. Conclusions This report highlights genetic alterations, in particular an acquired somatic KRAS mutation, that may occur during transdifferentiation, with additional significance of KRAS mutation as a possible therapeutic target in cases which otherwise would have limited treatment options.